2000
DOI: 10.2307/4003392
|View full text |Cite
|
Sign up to set email alerts
|

Response of 2 Semiarid Grasslands to Cool-Season Prescribed Fire

Abstract: Woody perennials have invaded semiarid grasslands throughout the Southwestern United States. This invasion was coupled with decreased grass cover and increased runoff and soil erosion. Fire, which was a natural force that shaped and maintained the grasslands, is a management tool that may aid in restoring and maintaining grass cover. However, fire also poses the risk of increasing erosion and further soil degradation because protection afforded by vegetation is reduced immediately after the fire. Using a rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 16 publications
1
19
0
1
Order By: Relevance
“…Unfortunately, data are too limited concerning soil responses to fire for robust statements to be made about how soil temperature, moisture or nutrients relate to vegetation responses. Several authors noted that climatic and geographic variability had effects at least as great as fire and some interactions between climate or site and fire were reported (Biondini et al, 1989;Dix, 1960;Engle and Bultsma, 1984;White and Loftin, 2000;Whisenant and Uresk, 1989;White et al, 2006).…”
Section: Literature Synthesismentioning
confidence: 95%
“…Unfortunately, data are too limited concerning soil responses to fire for robust statements to be made about how soil temperature, moisture or nutrients relate to vegetation responses. Several authors noted that climatic and geographic variability had effects at least as great as fire and some interactions between climate or site and fire were reported (Biondini et al, 1989;Dix, 1960;Engle and Bultsma, 1984;White and Loftin, 2000;Whisenant and Uresk, 1989;White et al, 2006).…”
Section: Literature Synthesismentioning
confidence: 95%
“…High temperature burns causes the greatest volatile losses of nitrogen, while ash from lower intensity fires can contain large amounts of ammonium (DeBano et al 1998). Ash can also stimulate microbial activity, affecting CO 2 production and increase the amount of mineralizable N in the soil (White and Loftin 2000). Sometimes, N 2 O emissions have been reported to be higher from untilled soil than tilled soil (Linn and Doran 1984;MacKenzie et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…lternet.edu). Related research on these areas is reported in White and Loftin (2000), White et al (2004), and White et al (2006). All areas had domesticated livestock excluded for 20 yr to 30 yr prior to the fires.…”
Section: Study Areasmentioning
confidence: 98%
“…Microtopographic relief was measured with a removable soil bridge that has 31 bushings spaced at 5-cm intervals (White and Loftin 2000;White et al 2006;Ravi et al 2009). Each bridge site has two pieces of reinforcement bar that are driven into the soil to a depth of about 40 cm and fit into holes on the soil bridge so that the bridge was level when in place.…”
Section: Soil Microtopography Measurementsmentioning
confidence: 99%
See 1 more Smart Citation